Faktor yang Berhubungan dengan Beban Caregiver dalam Merawat Keluarga yang Mengalami Stroke - Yolla Nandha Ariska; Prita Adisty Handayani; Elis Hartati (Master of Nursing, Faculty of Medicine, Universitas Diponegoro, Indonesia, 2020)
Introduction: Stroke is a disease that most often causes disability in the form of paralysis of the limbs, speech disorders, thought processes and other forms of disability. In this condition, stroke patients need caregiver assistance to meet their daily needs. The caregiver faces physical, psychological, social, economic problems in providing care. This study aimed to determine the factors associated with caregiver burden in caring for family members suffering from stroke. Methods: This was a quantitative study with a cross sectional design. The research instrument used the Zarit Burden Interview questionnaire. The study recruited 56 caregivers as the sample with the inclusion criteria of caregivers aged ≥ 26 years old, providing care for stroke patient as a main caregiver in at least 3 monthsduration of care. The samples were selected by applying purposive sampling technique, and the data were analyzed by Chi Square test. Results: The study shows a significant relationshipbetween age (p=0.009), gender (p=0.001), employment status (p=0.002), income (p=0.000), marital status (p=0.025), family relationship (p=0.011), family support (p=0.000) and caregiver burden, however no correlation was identified between education and caregiver burden (p = 0.155). Conclusion: Age, gender, employment status, income, marital status, family relationships and family support are significantly related to the burden of caregivers in caring for stroke family members. Health services are expected to adequately provideinformation for caregivers related to how to care for stroke patients, in order to reduce the caregiver's burden.